Facing a Care Crunch: Childcare Disruption and Economic Hardships for Maine Parents during COVID-19 - Small, Sarah (Maine Policy Review, 2022)
Pandemic-related childcare center closures along with virtual schooling forced many Maine parents to juggle their paid work with care responsibilities, often with dire economic consequences. In this article, I examine changes in the state’s childcare landscape and illustrate how the childcare crisis during the COVID-19 pandemic affected Mainers’ economic wellbeing. Using Household Pulse Survey data, I show how care disruptions dampened Mainer’s incomes and their ability to work, placing many in precarious economic situations. I conclude with an investigation of the effectiveness of policy solutions like the Child Tax Credit and further policy suggestions to support childcare in the state.
Keywords: Childcare; COVID-19; Child Tax Credit; childcare workforce